Design of a PID Controller Circuit Employing CDBAs - Keskin, Ali Ümit (International journal of electrical engineering & education, 2006)
Proportional-integral-derivative (PID) controllers are one of the most important control elements used in the process control industry. In practice, voltage mode circuits (e.g., operational amplifiers) are largely used in analogue controllers. However, recent developments in the areas of nanotechnologies and micro-electromechanical systems (MEMS) necessitate fast operating active analogue circuits. This paper presents a PID controller circuit based on a newly introduced active universal component, so-called current differencing buffered amplifier (CDBA), and shows that the circuit performs quite well as a PID controller and offers the benefits of a current mode structure. An example is given to illustrate the application of this new active element. The development of the overall circuit relies on concepts introduced in the frequency domain, therefore it can be used as material for undergraduate-graduate circuits, systems and control courses.